Renewable energies: a commitment to ecocentrism and the rights of nature - Jiménez-García, Ángela María Jimena (Iberoamerican Journal of Development Studies, 2025)
The objective of this article is to analyze renewable energies (RE) from the viewpoint of ecocentrism and the rights of nature. It initially uses the theory of planetary limits to understand the current ecological crisis. It starts with the vicissitudes surrounding the energy transition, and then delves into the epistemological shift between the paradigms of anthropocentrism, biocentrism and ecocentrism. Next, the anthropocentric paradigm is identified as the prevailing paradigm in the regulation of RE in the world. Based on this, an alternative approach is proposed to view renewable energies through the lens of ecocentrism and the rights of nature. In sum, a «6-ecos» proposal is presented to move towards a regulation of RE in an ecocentric key: «ecointerests», «ecoethics», «ecoeconomics», «legal ecohermeneutics», «ecosubjects of law», and «ecoquipnayra».
Keywords: Renewable energies; anthropocentrism; ecocentrism; rights of nature